Adequacy of a Compartment Model for CMRO2 Quantitation Using 15O-Labeled Oxygen and PET: A Clearance Measurement of 15O-Radioactivity Following Intracarotid Bolus Injection of 15O-Labeled Oxyhemoglobin on Macaca Fascicularis. Issue 9 (September 2014) - Iida, Hidehiro; Iguchi, Satoshi; Teramoto, Noboru; Koshino, Kazuhiro; Zeniya, Tsutomu; Yamamoto, Akihide; Kudomi, Nobuyuki; Moriguchi, Tetsuaki; Hori, Yuki; Enmi, Junichiro; Kawashima, Hidekazu; Shah, Nadim Joni; et al.
We aimed at evaluating the adequacy of the commonly employed compartmental model for quantitation of cerebral metabolic rate of oxygen (CMRO2 ) using 15 O-labeled oxygen ( 15 O2 ) and positron emission tomography (PET). Sequential PET imaging was carried out on monkeys following slow bolus injection of blood samples containing 15 O2 –oxyhemoglobin ( 15 O2 –Hb), 15 O-labeled water (H2 15 O), and C 15 O-labeled hemoglobin (C 15 O–Hb) into the internal carotid artery (ICA). Clearance slopes were assessed in the middle cerebral artery territory of the injected hemisphere. The time–activity curves were bi-exponential for both 15 O2 –Hb and H2 15 O. Single exponential fitting to the early (5 to 40 seconds) and late (80 to 240 seconds) periods after the peak was performed and the 15 O2 –Hb and H2 15 O results were compared. It was found that a significant difference between the clearance rates of the 15 O2 –Hb and H2 15 O injections is unlikely, which supports the mathematical model that is widely used to describe the kinetics of 15 O2 –Hb and H2 15 O in cerebral tissues and is the basis of recent approaches to simultaneously assess CMRO2 and cerebral blood flow in a single PET session. However, it should be noted that more data are necessary to unequivocally confirm the result.